God and Human Sovereignty in Islamic Political Tradition - Ridwan Ridwan; Muhammad Fuad Zain (Ijtimā`iyya: Journal of Muslim Society Research, 2020)
The debate on the concept of political sovereignty leads to the question of whether sovereignty comes from God or humans. It is related to the foundation of state management and has implications for the political system. Islamic political tradition has not an authoritative text that explains sovereignty. This thesis was conducted based on the evidence of Islamic political history which did not present a concept of universal and standard sovereignty. Muslim thinkers proposed some alternative ideas of sovereignty such as nomocratic, theo-democracy and democracy. The author sees that the sovereignty concept in Islam is discussed as ijtihaÌ„diyyah (intellectual interpretation and judgment) which lead to multiple interpretations in some contemporary Muslim countries show that the sovereignty concept in Islam is dynamic and can be negotiated according to the political needs of the society.